POST-ADAPTIVE SURVIVAL MECHANISMS IN MYCOBACTERIUM TUBERCULOSIS: A COMPREHENSIVE REVIEW - PRASANTHI TULASI; SHOBHA SINGARAPALLE; MANAL NK HAMEM; MURALI KRISHNA KUMAR MUTHYALA (Asian Journal of Pharmaceutical and Clinical Research, 2026)
Mycobacterium tuberculosis (MTB) survives hostile host environments by activating complex post-adaptive survival mechanisms that enable long-term persistence and drug tolerance. Under conditions of nutrient deprivation, hypoxia, oxidative stress, and immune pressure, MTB activates metabolic reprogramming, cell wall remodeling, and regulatory networks. These responses contribute to phenotypic drug tolerance and complicate tuberculosis (TB) treatment outcomes. This review summarizes molecular, metabolic, and phenotypic post-adaptive mechanisms employed by MTB, with particular emphasis on post-translational modifications, stress-responsive pathways, and dormancy-associated processes. In addition, the clinical relevance of these adaptive strategies, including their impact on drug efficacy, treatment duration, and therapeutic failure, is critically discussed. A deeper understanding of post-adaptive survival mechanisms may facilitate the development of improved therapeutic strategies targeting persistent and drug-tolerant TB.